(untitled) (American Journal of Management, 2024)
This case study is designed to help business students explore the complexities of external environmental factors and their impact on businesses. The case is built around the story of the Italian Forum, a mixed-use development in Leichhardt, an inner west suburb of Sydney in Australia. The Italian Forum was built on classic Italian architecture design principles which includes a mix of residential, commercial and cultural space. The New South Wales State Government granted the land for the Forum to promote and preserve Italian culture. After the initial euphoria and success, the businesses in the Forum started facing many complex and insurmountable challenges which has led to closure of many businesses. The efforts to revive the Forum continue till date. Students are encouraged to examine all aspects of this live case to understand the challenges and propose realistic solutions, drawing on theories and models learned in business courses. Limitations of the study include reliance on secondary research and qualitative data, which may restrict the depth of analysis available in this case study.